CARE AND PHYSIOTHERAPEUTIC INTERVENTION IN THE REHABILITATION OF ELDERLY PATIENTS ATTENDED IN PRIMARY HEALTH CARE: EXPERIENCE REPORT - Callou Filho, Cesario Rui; Lima, Antonia Rayane De Sousa; dos Santos, Marina Lopes; Queiroz, Francisca Francisete de Sousa Nunes; Martins, Juliana Furtado; Augusto, Ana Lindaura Callou; Medina, Ligia Lucena Gonçalves; Jorge, Maria Salete Bessa (Seven Editora, 2026)
Introduction: This study describes the experience of a physiotherapist resident integrated into a multidisciplinary team within the Family Health Strategy (FHS) in the municipality of Quixeramobim, Ceará, Brazil, during the 2019–2020 period. It discusses the role of physiotherapy within the Brazilian Unified Health System (SUS), emphasizing health promotion, disease prevention, and rehabilitation actions carried out in an integrated manner with families and the community. Collective activities included prenatal groups, exercise programs for older adults, postural assessments, and follow-up of individuals with acute respiratory infections, among others.Objective: To describe the experience of a physiotherapist in managing musculoskeletal pain in older adults participating in a health promotion program.Methods: This is an experience report conducted over eight months, from August 2019 to March 2020, at the FHS unit Luís Prata Girão, located in the Conjunto Esperança neighborhood in Quixeramobim, Ceará.Results: The intervention led to a significant reduction in pain levels, decreased medication use, and improved social and family reintegration among participants.Conclusion: The multidisciplinary team approach contributed to positive outcomes, high participant adherence, and strengthened comprehensive care. The inclusion of physiotherapy in primary health care proved essential for risk reduction, lifestyle modification, physical and psychosocial development, as well as for enhancing preventive and rehabilitative health actions.